2014
DOI: 10.4104/pcrj.2014.00003
|View full text |Cite
|
Sign up to set email alerts
|

Predicting asthma in preschool children at high risk presenting in primary care: development of a clinical asthma prediction score

Abstract: Background: A setting-specific asthma prediction score for preschool children with wheezing and/or dyspnoea presenting in primary healthcare is needed since existing indices are mainly based on general populations. Aims: To find an optimally informative yet practical set of predictors for the prediction of asthma in preschool children at high risk who present in primary healthcare. Methods: A total of 771 Dutch preschool children at high risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 30 publications
0
30
0
3
Order By: Relevance
“…Severe recurrent wheezing (indicated by at least two previous hospital admissions due to exacerbation) was an independent predictor of current asthma at the age of 13 years among a population of recurrent wheezing children aged under 36 months (OR=2.3; 95% CI: 1.3–4.2; p =0.007) 26. Wheezing-induced sleep disturbances and wheezing in the absence of a cold were identified as two of the five independent predictors of asthma diagnosis at age 6 (OR=2.08; 95% CI: 1.31–3.29; p =0.002, and OR=2.22; 95% CI: 1.23–3.99; p =0.008, respectively) 17. Wheezing without colds, exercise-related wheeze/cough (wheeze or a cough with running, playing, laughing, or crying), and more than three episodes of wheezing attacks (OR=1.40; p <0.001, OR=1.26; p <0.001, and OR=1.65; p <0.001, respectively) were three of ten predictor variables included in the tool proposed for predicting asthma at school age 18.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Severe recurrent wheezing (indicated by at least two previous hospital admissions due to exacerbation) was an independent predictor of current asthma at the age of 13 years among a population of recurrent wheezing children aged under 36 months (OR=2.3; 95% CI: 1.3–4.2; p =0.007) 26. Wheezing-induced sleep disturbances and wheezing in the absence of a cold were identified as two of the five independent predictors of asthma diagnosis at age 6 (OR=2.08; 95% CI: 1.31–3.29; p =0.002, and OR=2.22; 95% CI: 1.23–3.99; p =0.008, respectively) 17. Wheezing without colds, exercise-related wheeze/cough (wheeze or a cough with running, playing, laughing, or crying), and more than three episodes of wheezing attacks (OR=1.40; p <0.001, OR=1.26; p <0.001, and OR=1.65; p <0.001, respectively) were three of ten predictor variables included in the tool proposed for predicting asthma at school age 18.…”
Section: Resultsmentioning
confidence: 94%
“…Also, age (years) was positively correlated with a greater probability of asthma at the age of 6 years in the multivariable analysis in the Airway Complaints and Asthma Development (ARCADE) study (OR=1.47; 95% CI: 1.24–1.75; p <0.001) 17. Age >1 year was one of the ten predictor variables included in the tool proposed by Pescatore et al18 Likewise, Reijonen et al identified age ≥12 months on entry as an independent predictor of asthma at the median age of 4 years (OR=4.1; 95% CI: 1.59–10.35; p =0.0034) 27…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Several models of risk were generated to help identify those children who will continue wheezing into school age. [73][74][75][76][77][78][79][80][81] These models use risk factors associated with the development of asthma in epidemiologic studies such as a parental history of allergic sensitization, recurrent wheezing history, atopic disease in the child, increased IgE levels, decreased lung function, elevated exhaled nitric oxide, and increased T-helper-4 cytokine levels. One of the most studied, the Asthma Predictive Index (API), 73 was derived from the Tucson study data that includes risk factors, such as frequent wheezing, a parental history of asthma, and signs of personal atopic disease.…”
mentioning
confidence: 99%